2020
DOI: 10.1136/bcr-2020-237336
|View full text |Cite
|
Sign up to set email alerts
|

Subacute thyroiditis associated with COVID-19

Abstract: We report a case of a hospitalised patient with COVID-19 who developed subacute thyroiditis in association with SARS-COV-2 infection. The patient presented with tachycardia, anterior neck pain and thyroid function tests revealing hyperthyroidism together with consistent ultrasonographic evidence suggesting subacute thyroiditis. Treatment with corticosteroids resulted in rapid clinical resolution. This case illustrates that subacute thyroiditis associated with viruses such as SARS-CoV-2 should be recognised as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 8 publications
3
114
0
9
Order By: Relevance
“…We learned that both SARS and COVID-19 survivors had thyroid abnormalities. Based on the available results in the SARS-CoV-2 pandemic [18][19][20][21][22][23][24][25][58][59][60], more attention has to be paid both to patients with not diagnosed thyroid disorder and to treated thyroid patients with COVID-19. Routine control of thyroid function is not recommended by the guidelines however, we suggest the importance of monitoring thyroid hormones in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We learned that both SARS and COVID-19 survivors had thyroid abnormalities. Based on the available results in the SARS-CoV-2 pandemic [18][19][20][21][22][23][24][25][58][59][60], more attention has to be paid both to patients with not diagnosed thyroid disorder and to treated thyroid patients with COVID-19. Routine control of thyroid function is not recommended by the guidelines however, we suggest the importance of monitoring thyroid hormones in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Recently four cases of subacute thyroiditis (de Quervain's thyroiditis) have been reported in COVID-19 patients [19][20][21][22]. Thyroid function assessments showed thyrotoxicosis, with suppressed serum TSH, elevated fT4, fT3 and thyroglobulin levels as well as the absence of thyroid autoantibodies.…”
Section: Sars-cov-2 and Thyroidmentioning
confidence: 99%
“…In fact, cases of thyroxine thyrotoxicosis have been also described (318). Several case reports and a case series were focused on the prevalence of subacute thyroiditis and thyroxine thyrotoxicosis in patients with severe presentation of COVID-19 from ICU (319)(320)(321)(322)(323)(324). More recently in a retrospective study on 50 COVID-19 patients it was found a decrease in total T3 and TSH concentrations in 56% of patients (325)(326)(327).…”
Section: Thyroidmentioning
confidence: 99%
“…Although the pulmonary system is the main target of SARS-CoV2 infection [1], extrapulmonary organs can be affected with potential negative impact on clinical outcome of COVID-19 [2]. Interestingly, alterations of thyroid hormones resembling a subacute thyroiditis (SAT) have been consistently reported in a substantial number of subjects with COVID-19 [3][4][5][6][7][8][9][10][11], prompting to hypothesize that thyroid gland may be a frequent target of SARS-CoV2 infection [12,13]. However, the clinical relevance of thyrotoxicosis associated with SARS-CoV2 infection is still controversial [3,14,15,4] and data on the outcome of thyroid function after remission of COVID-19 are scanty [14].…”
Section: Introductionmentioning
confidence: 99%